Peningkatan Perilaku Sosial Santri melalui Peran Wali Asuh di Pesantren - Efendi, Are; Zahid, Reza Ahmad; Makhfud, Makhfud; Fajar, Abbas Sofwan Matla'il (Kartika: Jurnal Studi Keislaman, 2023)
This study explores ways to improve students' social behavior through the role of foster guardians in Islamic boarding schools. This study uses qualitative research methods. The data sources are interviews with key informants, the heads and administrators of Islamic boarding schools, and observations. This research shows that Islamic boarding schools have unique methods for improving students' social behavior. The indicator is the active involvement of foster guardians in implementing the Islamic boarding school program. There are three types of programs implemented by foster guardians to improve the social behavior of students, including routine recitation, cleanliness pickets, and social service. The implementation of these three programs has supporting and inhibiting factors. Supporting factors for foster guardians to improve the social behavior of students, such as cooperation and discipline between foster guardians to help the administrators with their duties so that it is easier for their foster children to carry out Islamic boarding school activities. In contrast, inhibiting factors are lack of coordination, cooperation, and conflicts in the foster guardian's activity schedule.